Sapphire-Based Planar Bragg Grating Devices - Kefer, Stefan; Schmauß, Bernhard; Hellmann, Ralf (Proceedings - 28th International Conference on Optical Fiber Sensors, OFS 2023, 2023)
This study reports on the long-term stability and the high-temperature capability of sapphire-based photonic crystal waveguides with integrated Bragg gratings. Furthermore, their Bragg grating reflectivity as well as their temperature sensitivity is quantified.
CRIS-Team Scopus Importer:2024-12-16